Geomorphological and Environmental Characteristics of the Al-Mashab and Al-Salal Marshes, Southern Iraq - Hassan, Zainab D. (Iraqi Journal of Science, 2025)
Marshes are a geomorphological phenomenon found in southern and southeastern Iraq. The study area is part of these wetlands located in an arid region, which play a significant role in softening the region's climate as well as its economic and tourist importance. The objective is to assess the environmental geomorphology of the marshes west of Basra, specifically the marshes of Al-Mashab and Al-Salal. Soil and water samples were collected through fieldwork, and the physical, and chemical of the major elements were conducted.The study area is polluted with high concentrations of major elements in both water and soil compared to the Iraqi and global standards. The north part of the study area shows a high EC value of 17 s/cm, TDS3090 mg/l, chloride 1813 mg/l, sulfate 800mg/l  and calcium 350mg/l as well as high concentrations of sodium (42000ppm, calcium 35000ppm, sulfate  11280ppm, chloride 24802ppm). The digital processing and analysis results of satellite visualizations were adopted in the Erdas V.2014 and GIS software V10.4 by applying the equations of the NDWI water guide and the normalized difference vegetation index (NDVI) and designing a mathematical model in the GIS program to detect the change during the study period (1973-2016). The increase in vegetation cover in 1973 shows that water was the largest area during the studied period by 5 km2 in 2016. The area of the intersecting area that has not been subjected to change for water is 5.5 km2 and for vegetation cover is 8.7 km2.